Validation of Axial Juvenile Spondyloarthropathy Criteria in Turkish Juvenile Spondyloarthropathy Patients - Dilara Unal; Cansu Ayten Tatar; Erdal Sag; Yagmur Bayindir; Emil Aliyev; Veysel Cam; Hulya Ercan Emreol; Mehmet Orhan Erkan; Ozge Basaran; Yelda Bilginer; Seza Ozen (Diagnostics, 2025)
Background: Juvenile spondyloarthritis (JSpA) is a heterogeneous group of diseases. An international consensus group developed the axial juvenile SpA (AxJSpA) classification criteria for this purpose, defining a homogeneous group of patients diagnosed with jSpA and experiencing axial symptoms before the age of 18 years. Aim: To validate this new set of criteria in our pediatric SpA patients. Methods: This study was held in the Hacettepe University Department of Pediatric Rheumatology. Juvenile SpA patients suspected of axial disease diagnosed and followed at the same center between 2005 and 2024 were included. Patients who had other etiologies for axial symptoms, including chronic nonbacterial osteomyelitis, mechanical back pain–overuse injuries, amplified pain/growing pains, and SAPHO syndrome (synovitis, acne, pustulosis, hyperostosis, and osteitis) served as the control group. Results: In total, 123 JSpA patients and 74 controls were included in this study. The sensitivity/specificity of the new criteria were 61%/77% with an area under curve value of 0.75 (95% CI: 0.68–0.83) in our cohort. Among different criteria sets, European Spondyloarthropathy Study Group (ESSG) criteria were the most sensitive (sensitivity/specificity 91%/68%), and ASAS peripheral criteria (Assessment of SpondyloArthritis International Society) were the most specific (sensitivity/specificity 67%/84%) in our cohort when compared to ASAS axial criteria (sensitivity/specificity 74%/65%), ILAR (International League of Associations for Rheumatology) (sensitivity/specificity 85%/81%), and ILAR + SI (sacroiliitis) (sensitivity/specificity 67%/74%) criteria. Conclusions: The area under the curve of the new AxJSpA criteria was similar to that of the original report; however, both sensitivity and specificity were lower in our cohort, possibly due to factors like earlier disease presentation and a lower prevalence of chronic structural changes on MRI.